PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN (Study Pada Karyawan Rumah Sakit Islam Banjarmasin) - Winda Andriyani; Rahmi Widyanti; Husnurrofiq Husnurrofiq (Al-KALAM : JURNAL KOMUNIKASI, BISNIS DAN MANAJEMEN, 2020)
This study aims to determine and analyze Effect of Work Environment and Work Discipline on Employee Performance (Study on Islamic Hospital Banjarmasin), this type of research is quantitative research. Sample taken counted 77 respondents by using Slovin formula. Data collection is taken by usung some technique that is observation, interview, and quetioner by using Likert scale., Statistical analysis using IBM Statistic application version 20.Based on the result of calculations and testing result obtained work environmentvariables   partially   affect  the  employe  performance   with  tcount3.747>ttable1.667, variable work discipline partially affect the employe performance with tcount4.011>ttable1.667, variable work environment and work discipline partially affect the employe performance with Fcount35.406 > Ftable3.155. The result of subsequent testing based on the coefficient of determination obtained partial work environment effect on employee performance with the regression is 0.378 or 37.8%, the effect of work discipline partially on employee performance with the value of regression is equal to0.392 or 39.2 %, and the last test result effect of work environment and work discipline on employee performance with the regression is 0.489 or 48.9%.The result of this study can be a reference for various parties to improve employee perpormance. It is necessary to continuously  develop employees through work environment. In addition, there should also be attention to work discipline in the organization of the employees.